Legislative principles of information security provision in the European Union member states - Bratsuk, Ivan; Kavin, Svyatoslav (Vilnius University Open Series, 2020)
The article is dedicated to the study of the information security provision in the EU Member States in the context of analyzing their state programs, national programs as well as regulatory legal acts. This study identifies priorities and gaps in the information security provision in the EU Member States, analyzes special features of the institutional and legal mechanism of information security in the EU Member States in the context of the multi-vector international security system. The expediency of developing an integral coordinated information policy of the EU Member States, aimed at unification of the approaches to information security, is substantiated, as well as the experience of the EU Member States in this field aimed at improving the domestic regulatory framework of information security provision is studied.